DAMPAK COVID-19 TERHADAP KINERJA PERUSAHAAN PROPERTI DAN REAL ESTATE DI INDONESIA TAHUN 2019 DIBANDINGKAN TAHUN 2020 - Alamsyah, Nabilah Putri (Banking & Management Review, 2022)
The purpose of this study was to determine the impact of the coronavirus on the performance of companies in the property real estate sector in Indonesia. In this study, the company's performance can be measured by the current ratio, debt to equity ratio, total asset turnover, and return on assets. This study uses secondary data from property and real estate financial statements on the Indonesia Stock Exchange and uses property and real estate companies that have been listed on the Stock Exchange. The data analysis method used the Wilcoxon signed rank test, which had been tested for normality before using SPSS version 25. The results of data analysis show that the current asset ratio, even though it experienced a decline, the company was not affected by the COVID-19 pandemic. Although the pandemic had an effect, it increased, while the ratio of total asset turnover and return on assets experienced a significant difference because it decreased compared to before the COVID-19 pandemic.